Cutting frequency on quality indicators of Pennisetum and Saccharum varieties during the dry period - Herrera, Rafael Segundo; Mart?nez, Ram?n Omar; Mart?nez, M.; Tuero, Ra?l; Cruz, Ana Mar?a; Romero, Aida (Cuban Journal of Agricultural Science, 2014)
A random block design with five replications and thirteen treatments was applied. Treatments consisted of three varieties of Pennisetum purpureum (king grass, Cuba CT-115 and Cuba CT-169) cut two (August and February), four (May, July, September and February) and five times a year (November, February, May, July and September) and two of Saccharum officinarum (Jaron? 60-5 and Villa Clara 21), cut one (February) and two (February and August) times a year for determining their influence on some forage quality indicators. The experiment was conducted in a red ferrallitic soil for four years with fertilization (100-60-80 kg/ha/year of N, P2O5 and K2O, respectively) and irrigation during the dry period. There were differences (P < 0.001) in the CP content of the varieties according to the cutting frequency. The highest values were registered in leaves, stems and the whole plant of the Pennisetum varieties with ranging values of 7.6-10, 4.2-5.9 and 5.1-7.3 %, respectively when cut five times a year. Crude fiber differed (P < 0.001) and the lowest values were recorded in the Pennisetum varieties with the highest cutting frequency. For in vitro organic matter digestibility there were differences (P < 0.001) favorable to the highest cutting frequency. Best results were attained when the Pennisetum varieties were cut five times per year. Cutting Saccharum two times per year propitiated the disappearance of Jaron? 60-5 at the end of the second year of study. The best balance of the studied indicators was obtained when Pennisetum and Saccharum varieties were cut five and once per year, respectively. There is available information that will allow improving the management of these varieties, for using them efficiently and attaining greater longevity of the plantation. Key words: protein, fiber, digestibility, forages